How protective is breast feeding against diarrhoeal disease in infants in 1990s England? A case-control study. Issue 3 (24th November 2005) - Quigley, M A; Cumberland, P; Cowden, J M; Rodrigues, L C
Abstract : Aims: To assess the effect of several measures of infant feeding on diarrhoeal disease, and whether these effects vary according to markers of social deprivation. Methods: Case-control study of diarrhoeal disease cases presenting to 34 general practices in England. Controls were stratified on age group, area deprivation index for the practice, and whether or not the practice was in London. Data were available on 304 infants (167 cases and 137 controls). Results: After adjustment for confounders, breast feeding was associated with significantly less diarrhoeal disease. Associations were striking even in infants aged ⩾ 6 months. They did not vary by social class, but were greater in those living in rented council accommodation and in more crowded households. The effect of receiving no breast milk was stronger in more deprived areas than in less deprived areas. The effect of not receiving exclusive breast milk was stronger in more deprived areas than in less deprived areas. In formula fed infants, there was significantly more diarrhoeal disease in those not sterilising bottles/teats with steam or chemicals. The protective effect of breast feeding did not persist beyond two months after breast feeding had stopped. Conclusions: Breast feeding protects against diarrhoeal disease in infants in England although the degree of protection may vary across infants and wear off after breast feeding cessation. Education about the benefits of breast feeding and the risks of inadequate sterilisation should be targeted at carers in deprived areas or households.